Convergence of Stochastic Proximal Gradient Algorithm - Rosasco, Lorenzo; Villa, Silvia; Vũ, Bằng Công (Applied mathematics & optimization, 2020)
We study the extension of the proximal gradient algorithm where only a stochastic gradient estimate is available and a relaxation step is allowed. We establish convergence rates for function values in the convex case, as well as almost sure convergence and convergence rates for the iterates under further convexity assumptions. Our analysis avoid averaging the iterates and error summability assumptions which might not be satisfied in applications, e.g. in machine learning. Our proofing technique extends classical ideas from the analysis of deterministic proximal gradient algorithms.